Bicomponent Assembly of VO2 and Polyaniline‐Functionalized Carbon Nanotubes for the Selective Oxidation of Biomass‐Based 5‐Hydroxymethylfurfural to 2, 5‐Diformylfuran. Issue 12 (19th August 2015) - Guo, Yuanyuan; Chen, Jinzhu
Abstract: Vanadium dioxide (VO2 ) immobilized on polyaniline‐functionalized carbon nanotubes (CNTs) (VO2 ‐PANI/CNT) was prepared for an aerobic oxidation of biomass‐based 5‐hydroxymethylfurfural (HMF) to 2, 5‐diformylfuran (DFF) by a bicomponent assembly method, and its structure was characterized by Raman, Brunauer–Emmett–Teller (BET), X‐ray diffraction (XRD), high‐resolution transmission electron microscopy (HRTEM), and X‐ray photoelectron spectroscopy (XPS) technologies. In the reaction system, homogeneously dispersed VO2 nanoparticles were produced by a spontaneous redox process between VO3 − anions and the PANI moiety of the PANI/CNT composite material. The PANI/CNT support shows a preferential adsorption to reactant HMF than in the case of product DFF, which can be used as a promoter to prevent the further oxidation of DFF. Hence, compared with other vanadium catalysts, VO2 ‐PANI/CNT shows excellent catalytic performance for the selective oxidation of HMF to DFF with molecular oxygen as oxidant. In addition, the reaction parameters such as reaction time, reaction temperature, vanadium content, oxygen pressure, and solvent were investigated and a maximum DFF yield of 96 % with a full HMF conversion was observed. Abstract : Selective oxidation : VO2 immobilized on polyaniline‐functionalized carbon nanotubes (CNTs), by means of a spontaneous redox‐induced bicomponent assembly route, efficiently promotes the selective oxidation of biomass‐based 5‐hydroxymethylfurfural to 2, 5‐diformylfuran (see scheme).